Physiotherapy improves motor function in patients with the Parkinson variant of multiple system atrophy: A prospective trial - Raccagni, C.; Goebel, G.; Gaßner, Heiko; Granata, Roberta; Ndayisaba, Jean Pierre; Seebacher, Barbara; Schoenherr, Gudrun; Mitterhuber, Jakob; Hendriks, Pascalle; Kaindlstorfer, Christine; Eschlboeck, Sabine; Fanciulli, Alessandra; et al. (Parkinsonism & Related Disorders, 2019)
Background and objectives: Gait impairment and reduced mobility are disabling symptoms of multiple system atrophy. While physiotherapy is increasingly recognized as a valuable supplement to pharmacotherapy for patients with Parkinson's disease, data on the efficacy of physiotherapy for multiple system atrophy are lacking. This study aimed to explore the feasibility of two consecutive exercise-based interventions in patients with multiple system atrophy. Subjects and Methods: We included 10 patients with the parkinsonian variant of multiple system atrophy and 10 patients with Parkinson's disease, matched for gender and Hoehn & Yahr stage (≤3). Interventions consisted of a five-day inpatient physiotherapy program followed by a five-week unsupervised home-based exercise program. Outcomes included instrumented gait analysis, patient questionnaires, clinical rating scales and physical tests. Patients were examined at baseline, after the first inpatient treatment and again after the home-based intervention. Additionally, a structured telephone interview was performed immediately after the second intervention period. Results: Both patient groups exhibited a similar improvement of gait after the interventions, as measured by instrumented gait analysis. These effects reached their maximum level after inpatient physiotherapy and remained stable following the home-based exercise program. Patient questionnaires also showed improvements after the interventions, but motor clinical rating scales did not. Conclusion: Our pilot results suggest that a short-term bout of physiotherapy is feasible, safe and improves gait performance in patients with multiple system atrophy. This highlights the potential of physiotherapy for this disabling condition where pharmacotherapy typically achieves poor effects. The present findings warrant a larger controlled study.
CRIS-Team Scopus Importer:2019-10-01
Keywords: Atypical parkinsonian disorders; Home-based training; Multiple system atrophy; Parkinson's disease; Physiotherapy